2012
DOI: 10.5581/1516-8484.20120107
|View full text |Cite
|
Sign up to set email alerts
|

Hematological differences between patients with different subtypes of sickle cell disease on hydroxyurea treatment

Abstract: Objective Sickle cell anemia and the interaction S/Beta thalassemia differ in hematological values due to microcytosis and hypochromia caused by the thalassemic mutation. The clinical benefit of long-term hydroxyurea treatment is undeniable in sickle cell disease with monitoring of the biological action of the drug being by the complete blood count. The objective of this work is to compare changes in some of the erythrocytic indexes between S/Beta thalassemia and sickle cell anemia patients on long-term hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…In agreement with our results, Hashemi et al in a study indicated that Hydroxyurea treatment decreases the numbers of regular transfusion requirement ( Hashemi et al, 2009 ). Moreover, another study in harmony with our findings by Neves et al showed HU treatment for the duration of one year significantly increases MCV in patients with sickle cell disease ( Neves et al, 2012 ). As mentioned before the valuable effects of HU are fetal hemoglobin induction, decreased cell adhesive properties, inflammation and hypercoagulability ( Karimi et al, 2005 ; Segal et al, 2008 ).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, Hashemi et al in a study indicated that Hydroxyurea treatment decreases the numbers of regular transfusion requirement ( Hashemi et al, 2009 ). Moreover, another study in harmony with our findings by Neves et al showed HU treatment for the duration of one year significantly increases MCV in patients with sickle cell disease ( Neves et al, 2012 ). As mentioned before the valuable effects of HU are fetal hemoglobin induction, decreased cell adhesive properties, inflammation and hypercoagulability ( Karimi et al, 2005 ; Segal et al, 2008 ).…”
Section: Discussionsupporting
confidence: 91%
“…The effect of HU on hemoglobin F production is one of its multiple mechanisms of action. HU effectively decreases the frequency of acute complications such as VOCs and ACS, and improves the rheological characteristics of RBCs, as previously reported [38]. However, there are patients with low HbF levels with moderate disease and others with high HbF levels with severe SCD.…”
Section: Plos Onesupporting
confidence: 76%
“…(7) The general incidence of thalassemia trait and sickle cell hemoglobinopathy in India varies between 3 -17% and 1-44% respectively. (15) We observed the mean height in centimeters is134.44 cms(± 34.67) and weight in kilograms is 38.48 kg (±16.00) ( (9) There are high percentage of HbS ranging from 45.9 to 82, the mean is being 69.45. (Table No 6) Patients having high levels HbA (>3.5%) as well as HbS (67%) are determinant for Sickle cell beta thalassemia.…”
Section: Discussionmentioning
confidence: 85%
“…(5) Sickle cell beta thalassemia(Hb S/β 0 -Thal) is often clinically indistinguishable from sickle cell anemia in which the production of Hb A is abolished. (6,7) The beta thalassemia gene is acting on sickled red blood cells to induce microcytosis, hypochromia, and increased level Hb F. (9) Increased Foetal haemoglobin (HbF) causes an improvement of the circulatory competence of these cells, reduction of hemolysis, and a small increase in haemoglobin as well as packed cell volume. It is observed that the higher level of HbF in this double heterozygous condition may be useful by decreasing HbS polymerization and prevents crisis.…”
Section: Introductionmentioning
confidence: 99%